2017
DOI: 10.1111/jocd.12378
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous squamous cell carcinoma of the scalp extending to the skull: A case report and review of the literature

Abstract: Squamous cell carcinoma (SCC) of the scalp has increased prevalence in older patients and often presents later in life. Mohs micrographic surgery remains the most effective treatment in most cases. Delayed presentation may result in localized bony invasion or distant metastases. We present a case of an elderly woman presenting with extension of SCC into the parietal bone of the skull.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…Its incidence is poorly defined 48 , though like for OSCC, it is increasing. Prognosis is poor for OSCC and also for the <5% of cSCC that is metastatic to regional lymph nodes 4952 . Genetic stratification for both tumours is improving; for OSCC on The Cancer Genome Atlas (TCGA; a collection of >20,000 extensively-characterised primary tumours spanning 33 cancer types) and for cSCC in the literature 51,53 .…”
Section: Resultsmentioning
confidence: 99%
“…Its incidence is poorly defined 48 , though like for OSCC, it is increasing. Prognosis is poor for OSCC and also for the <5% of cSCC that is metastatic to regional lymph nodes 4952 . Genetic stratification for both tumours is improving; for OSCC on The Cancer Genome Atlas (TCGA; a collection of >20,000 extensively-characterised primary tumours spanning 33 cancer types) and for cSCC in the literature 51,53 .…”
Section: Resultsmentioning
confidence: 99%
“…The role of human papillomavirus has been proposed to be involved in its pathogenesis 46,47 . Advanced age is associated to a higher risk of metastatic spreading 43 . SCC is reported to be more frequent in men than in women 1 .…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…In a large retrospective cohort study on 15 784 SCC inpatients, the scalp was the most common anatomic location accounting for 30.6% of the cases. Other authors reported a prevalence of SCCs around 16% among STs, and a metastatic spreading to cervical lymph nodes is estimated to be around 16% 43 . Mohs micrographic surgery is considered a good treatment option offering a 5‐year survival cure rate of 99%, compared with traditional surgery at 86%.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Among tumors of the scalp, 16.6% are squamous cell carcinoma, making SCC the second most prevalent, after basal cell carcinoma [2]. In addition to increased age, risk factors for scalp SCC include chronic scarring, actinic damage, and a history of ionizing radiation [3].…”
mentioning
confidence: 99%